Composite conductive agent and preparation method thereof, positive pole piece and preparation method thereof, and battery

By carbonizing, ball milling and ozing the first conductive agent and mixing it with the second conductive agent, a composite conductive agent with an efficient conductive network is prepared, which solves the problem of imperfect conductive network in the prior art, and significantly improves the conductivity and charge and discharge efficiency of the battery.

CN119833244APending Publication Date: 2025-04-15FARASIS TECH (GANZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411939381.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the existing dry composite conductive agent preparation method, the conductive agent and the binder are unevenly dispersed, and the single component conductive agent conducting network is not perfect enough, resulting in insufficient strength of the electrode diaphragm and an increase in surface resistance, affecting battery performance.

Method used

By carbonizing, ball milling and ozing in an inert gas atmosphere, a carbonaceous structure with more conductive properties is formed, and then mixed with the second conductive agent, a composite conductive agent with a more efficient conductive network is prepared.

Benefits of technology

It significantly reduces the electrode impedance, improves the overall conductivity of the composite conductive agent, and enhances the charging and discharging efficiency and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833244A_ABST
    Figure CN119833244A_ABST
Patent Text Reader

Abstract

The invention discloses a composite conductive agent and a preparation method thereof, a positive pole piece and a preparation method thereof, and a battery, the preparation method of the composite conductive agent comprises the following steps: carbonizing a first conductive agent in an inert gas atmosphere to obtain the carbonized first conductive agent; performing ball milling on the carbonized first conductive agent to obtain a ball-milled first conductive agent; performing ozonization on the ball-milled first conductive agent to obtain an ozonized first conductive agent; and mixing the ozonized first conductive agent and the ozonized second conductive agent to obtain the composite conductive agent. The carbonized first conductive agent is introduced and compounded with the second conductive agent through the synergistic effect of ball milling and ozonization, a more efficient conductive network can be constructed, the overall conductive performance of the composite conductive agent is further improved, and therefore the problems that a conductive network of a traditional composite conductive agent is not perfect enough and the conductive efficiency is not high are solved; when the electrode is applied to a dry-method electrode, the electrode impedance can be obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite conductive agent and a preparation method thereof, a positive electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] At present, the conductivity of the commonly used positive electrode active materials such as lithium iron phosphate, lithium manganese oxide, and ternary materials is not high, and there is a large contact resistance between the positive electrode material particles. In order to increase the electron migration rate in the positive electrode and reduce the impedance of the electrode, the existing technology usually adopts a technical solution of adding a composite conductive agent with high conductivity in the preparation of the positive electrode.

[0003] A composite conductive agent is an additive composed of two or more different conductive materials, which can make the active material particles in the electrode conduct electrons better, reduce the resistance of electron transmission, and thus improve the charge and discharge efficiency and rate performance of the battery. However, the preparation process of the composite conductive agent determines the quality of its performance, and it directly affects the performance of the battery product after being used in the battery electrode. The existing preparation processes of composite conductive agents include wet electrode preparation processes and dry electrode preparation processes, wherein the preparation of dry composite conductive agents mainly involves mixing a single-component conductive agent and a binder powder, and then preparing an electrode through steps such as coating. For example, the Chinese invention patent application with publication number CN114758814A discloses a conductive composite material and a method for preparing the same, including subjecting a mixture of carbon nanotubes and a fluorine-containing polymer to spiral extrusion to obtain the conductive composite material.

[0004] In the above-mentioned existing dry electrode preparation process, the binder can bind the single-component conductive agents together and fill the gaps between the single-component conductive agents, so that electrons can pass through the connection parts between different single-component conductive agents when transmitting inside the conductive agent. However, in the above-mentioned existing dry preparation method, the single-component conductive agent and the binder are difficult to mix evenly. At the same time, in the conductive composite material obtained by spiral extrusion, the conductive network of the single-component conductive agent is not perfect and the conductive efficiency is not high. When used in the preparation process of dry electrodes, it is easy to cause the electrode membrane to be insufficient in strength and unable to form a film, resulting in an increase in the surface resistance and weak strength of the electrode membrane, which in turn affects the electrical properties of the electrode membrane, and its conductivity improvement is very limited. Therefore, it is urgent to study a method for preparing a composite conductive agent to improve the deficiencies of the above-mentioned existing dry composite conductive agent preparation method. Summary of the invention

[0005] The main purpose of the present invention is to provide a composite conductive agent and a preparation method thereof, a positive electrode sheet and a preparation method thereof, and a battery, aiming to solve the technical problems of uneven dispersion of the conductive agent and the binder in the existing dry composite conductive agent preparation process, imperfect conductive network of the single component conductive agent, and low conductive efficiency, which in turn lead to the performance of the electrode membrane being affected when it is used in the preparation of electrodes by dry method.

[0006] In order to achieve the above object, the present invention provides a method for preparing a composite conductive agent in a first aspect, comprising the following steps:

[0007] Carbonizing the first conductive agent in an inert gas atmosphere to obtain a carbonized first conductive agent;

[0008] ball-milling the carbonized first conductive agent to obtain a ball-milled first conductive agent;

[0009] ozonating the ball-milled first conductive agent to obtain an ozonated first conductive agent;

[0010] The ozonated first conductive agent is mixed with the second conductive agent to obtain the composite conductive agent.

[0011] Furthermore, the first conductive agent is one or more combinations of melamine foam, polyurethane foam and phenolic foam.

[0012] Furthermore, the second conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, and graphene.

[0013] Furthermore, by weight, the first conductive agent accounts for 2% to 10% of the composite conductive agent.

[0014] Furthermore, the particle size of the first conductive agent is 2 micrometers to 5 micrometers, and the particle size of the second conductive agent is 40 nanometers to 60 nanometers.

[0015] Furthermore, in the step of ozonating the ball-milled first conductive agent to obtain an ozonated first conductive agent, the mass concentration of ozone used for ozonation is 5-15 ug / l, and the ozonation reaction is carried out with the first conductive agent at a flow rate of 0.8-1.2 L / min.

[0016] Furthermore, before the step of carbonizing the first conductive agent in an inert gas atmosphere to obtain the carbonized first conductive agent, the step further includes: acid washing, water washing and drying the first conductive agent.

[0017] A second aspect of the present invention provides a composite conductive agent, which is prepared by any of the methods described above.

[0018] A third aspect of the present invention provides a positive electrode plate, which includes a current collector and a positive electrode material, and the positive electrode material includes the above-mentioned composite conductive agent, a positive electrode active material and a binder.

[0019] Furthermore, by weight, the positive electrode active material accounts for 94% to 98% of the positive electrode material, the composite conductive agent accounts for 1% to 3% of the positive electrode material, and the binder accounts for 1% to 3% of the positive electrode material.

[0020] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, which is used to prepare the positive electrode sheet as described in any one of the above items, comprising the following steps:

[0021] The positive electrode active material and the composite conductive agent are mixed uniformly to obtain a mixture;

[0022] adding a binder to the mixture and performing fiberization to obtain a fiberized mixture;

[0023] kneading the fiberized mixture to obtain a kneaded fiberized mixture;

[0024] Rolling the kneaded fiberized mixture to obtain a positive electrode film;

[0025] The positive electrode film is compounded with the carbon-coated aluminum foil to obtain the positive electrode plate.

[0026] Furthermore, the positive electrode film and the carbon-coated aluminum foil are pressed together at a temperature of 80 degrees Celsius to obtain the positive electrode plate.

[0027] A fifth aspect of the present invention provides a battery, comprising a positive electrode sheet as described in any one of the above items.

[0028] Beneficial effects:

[0029] Compared with the prior art, a method for preparing a composite conductive agent according to an embodiment of the present application includes carbonizing a first conductive agent in an inert gas atmosphere to obtain a carbonized first conductive agent; ball-milling the carbonized first conductive agent to obtain a ball-milled first conductive agent; ozonating the ball-milled first conductive agent to obtain an ozonated first conductive agent; and mixing the ozonated first conductive agent with a second conductive agent to obtain the composite conductive agent. The preparation method transforms the structure of the first conductive agent into a carbonaceous structure that is more conducive to electron conduction through a carbonization process, which can provide more conductive pathways, enhance the conductive properties, and improve the conductive properties of the original first conductive agent; at the same time, ball milling can refine the particles and increase the specific surface area of ​​the material, so that the contact between the first conductive agent and the second conductive agent is more complete and the mixing is more uniform; ozonation can improve the compatibility of the first conductive agent and the second conductive agent, allowing the two to be better combined. Through the synergistic effect of ball milling and ozonation, a more efficient conductive network can be constructed, and the overall conductive properties of the composite conductive agent can be further improved, thereby solving the problems of imperfect conductive networks and low conductive efficiency of traditional composite conductive agents. When applied to dry electrodes, the electrode impedance can be significantly reduced.

[0030] Compared with the prior art, the composite conductive agent of the embodiment of the present application is prepared by any of the above methods. It is understood that the composite conductive agent of the present application may include all the technical features and technical effects of the composite conductive agent prepared by the above preparation method.

[0031] Compared with the prior art, a positive electrode sheet of an embodiment of the present application includes any of the composite conductive agents described above. It is understandable that the positive electrode sheet of the present application can include all the technical features and technical effects of the composite conductive agent prepared by the above preparation method, which will not be repeated here.

[0032] Compared with the prior art, a method for preparing a positive electrode plate in an embodiment of the present application is used to prepare the positive electrode plate described in any of the above items, comprising adding a positive electrode active material and a composite conductive agent into a fiberizer, mixing them evenly to obtain a mixture; adding a binder to the mixture, mixing them evenly to obtain a fiberized mixture; kneading the fiberized mixture to obtain a kneaded fiberized mixture; rolling the kneaded fiberized mixture to obtain a positive electrode film; and compounding the positive electrode film with a carbon-coated aluminum foil to obtain the positive electrode plate. The preparation method utilizes the mechanical stirring effect of a fiberizer to fully contact the particles of the positive electrode active material and the composite conductive agent, and allows the composite conductive agent to be evenly distributed around the positive electrode active material. Conductive contact points can be formed on the surface of the positive electrode active material particles to construct a conductive network. After the binder is added, it is adsorbed on the surface of the positive electrode active material and the composite conductive agent particles and gradually wraps the particles, bonding the active material and the composite conductive agent together to form a stable connection between the particles to form a fiberized mixture. The banburying makes the distribution of the composite conductive agent between the positive electrode active material particles more uniform and continuous, the conductive path more perfect, and the resistance of electrons in the conduction process further reduced. The method can effectively solve the technical problems in the prior art that the composite conductive agent and the positive electrode active material cannot be fiberized and are unevenly mixed, which leads to an imperfect electrode conductive network, low conductive efficiency, and relatively high impedance.

[0033] Compared with the prior art, a battery in an embodiment of the present application includes any of the above-mentioned positive electrode sheets. It is understandable that the battery of the present application can include all the technical features and technical effects of the above-mentioned positive electrode sheets, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of a process for preparing a composite conductive agent in one embodiment of the present invention;

[0035] Figure 2 It is a schematic diagram of a process for preparing a positive electrode sheet in one embodiment of the present invention;

[0036] Figure 3 is a scanning electron microscope schematic diagram of carbonized melamine foam in one embodiment of the present invention;

[0037] Figure 4 Schematic diagram of the working principle of the composite conductive agent and the positive electrode active material in one embodiment of the present invention.

[0038] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0039] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0040] The charging and discharging process of lithium-ion secondary batteries is the process of lithium ions being intercalated and deintercalated back and forth between the positive and negative electrodes, accompanied by the transfer of electrons. During charging, lithium ions are extracted from the positive electrode, embedded in the negative electrode through the electrolyte, and electrons flow from the external circuit to the negative electrode; the opposite is true during discharge. The entire charging and discharging process requires the formation of effective electron and ion transmission channels inside the electrode material and between the electrode and the electrolyte. Therefore, the electrode needs to have good conductivity to ensure the smooth flow of electron transmission channels. Good conductivity can ensure that the electrode can conduct electrons quickly and efficiently. If the electrode conductivity is poor, the transmission of electrons inside the electrode material will be hindered, resulting in polarization of the battery during the charging and discharging process. Polarization will cause the operating voltage of the battery to deviate from its theoretical voltage, reduce the charging and discharging efficiency of the battery, and reduce the energy that the battery can store and release. At present, the conductivity of the commonly used positive electrode active materials such as lithium iron phosphate, lithium manganese oxide, and ternary materials is not high, and there is a large contact resistance between the particles of the positive electrode materials. In order to increase the electron migration rate in the positive electrode and reduce the impedance of the electrode, the prior art generally adopts a technical solution of adding a composite conductive agent with high conductivity in the preparation of the positive electrode.

[0041] In the prior art, commonly used conductive agents include granular conductive agents, such as conductive carbon black, metal powder, graphene, and composites of two or more different granular conductive materials. Although the above conductive agents can increase the contact probability with the positive electrode active material and reduce the internal resistance to a certain extent, the existing dry composite conductive agent and dry positive electrode sheet preparation method only adopts a simple mixing method to obtain a composite conductive agent dry powder, and then coats the positive electrode sheet for pressing, making it difficult for the conductive agent and the binder to be evenly mixed, and usually a single component of the conductive agent and the binder are mixed. In the obtained conductive composite material, the conductive network of the conductive agent is not perfect, the conductive efficiency is not high, and it is applied to the preparation process of the dry electrode. In the existing dry electrode preparation method, the composite conductive agent and the positive electrode material are mixed unevenly, the conductive sites are relatively few, and it is difficult to fiberize, which easily causes the electrode membrane to be insufficient in strength and unable to form a film, resulting in an increase in the surface resistance of the electrode membrane and weak strength, thereby affecting the electrical properties of the electrode membrane. Therefore, the conductivity of the composite conductive agent prepared by the preparation method in the prior art is very limited. Therefore, it is urgent to study a method for preparing a composite conductive agent to improve the shortcomings of the above-mentioned existing dry composite conductive agent preparation method.

[0042] In order to solve the technical problems that the conductive agent and the binder are unevenly dispersed in the above-mentioned existing dry composite conductive agent preparation process, the conductive network of the single component conductive agent is not perfect, and the conductive efficiency is not high, which leads to the technical problem that the electrode membrane performance is affected when it is applied to the dry electrode preparation electrode. The present invention application provides a preparation method of a composite conductive agent, through the carbonization process, the structure of the first conductive agent is transformed into a carbonaceous structure that is more conducive to electronic conduction, which can provide more conductive paths, enhance the conductive performance, and improve the conductive performance of the original first conductive agent; at the same time, ball milling can refine the particles, increase the specific surface area of ​​the material, make the contact between the first conductive agent and the second conductive agent more sufficient, and mix more evenly; ozonation can improve the compatibility of the first conductive agent and the second conductive agent, so that the two can be better combined, and through the synergistic effect of ball milling and ozonation, a more efficient conductive network can be constructed, and the overall conductive performance of the composite conductive agent can be further improved, thereby solving the problem that the conductive network of the traditional composite conductive agent is not perfect and the conductive efficiency is not high. When applied to the dry electrode, the electrode impedance can be significantly reduced. The following will be combined with the accompanying drawings to describe the preparation method of the composite conductive agent in the embodiment of the present application in detail.

[0043] An embodiment of the present invention provides a method for preparing a composite conductive agent, comprising the following steps:

[0044] S1: carbonizing the first conductive agent in an inert gas atmosphere to obtain a carbonized first conductive agent;

[0045] S2: ball-milling the carbonized first conductive agent to obtain a ball-milled first conductive agent;

[0046] S3: ozonizing the ball-milled first conductive agent to obtain an ozonated first conductive agent;

[0047] S4: mixing the ozonated first conductive agent and the second conductive agent to obtain the composite conductive agent.

[0048] In step S1, the first conductive agent is carbonized under an atmosphere of inert gas, which can prevent the first conductive agent from being oxidized during the high-temperature carbonization process. Carbonization is a pyrolysis process (pyrolysis refers to the process in which a substance decomposes a compound by heating under anaerobic or anoxic conditions to produce small molecule gases, liquids and solid residues). In this process, the organic components in the first conductive agent decompose and polycondense at high temperatures. Exemplarily, the polymer chains in the organic foam break at high temperatures, releasing small molecule gases, while the carbon atoms rearrange to form a more conductive carbonaceous structure. The conductivity and chemical stability of the first conductive agent are improved by the change of this structure. In the carbonized structure, the arrangement of carbon atoms is more orderly, forming a graphite-like layered structure or a carbon nanostructure, which is conducive to the conduction of electrons. At the same time, some of the original volatile and unstable components in the first conductive agent are removed, making the material more stable during subsequent processing and use.

[0049] Specifically, the first conductive agent is placed in a quartz crucible, and then the quartz crucible is placed in a tube furnace, and an inert gas is introduced for high-temperature heat treatment. The temperature rise stage is from 30°C to 800°C at a heating rate of 10°C / min, and the temperature is kept for 2h. The temperature holding stage is from 800°C to 950°C at a heating rate of 10°C / min, and the temperature is kept for 6h. In this embodiment, the temperature rises from 30°C to 800°C at a heating rate of 10°C / min, and this stage is a relatively mild heating process. For the first conductive agent, such a heating rate helps the organic components inside the material to gradually decompose. In the lower temperature range, some volatile small molecular components in the material (such as unreacted monomers, residual solvents, etc.) will evaporate first. At the same time, the polymer chain of the material begins to slowly undergo a pyrolysis reaction, the chemical bonds gradually break, and the carbon atoms begin to rearrange preliminarily. If the heating rate is too fast, it may cause excessive thermal stress inside the material, causing cracks or breakage in the material, affecting the structural integrity and performance after subsequent carbonization. This stage can gradually transform the structure of the first conductive agent into a carbonaceous structure, and at a relatively low temperature, the material can have enough time to adapt to the structural changes during the pyrolysis process, which is conducive to the formation of a relatively uniform preliminary carbonized structure. For example, for polyurethane foam, the urethane bonds in its molecular structure will gradually break at this stage, releasing small molecular gases, and at the same time, the three-dimensional network structure of the polyurethane foam will begin to transform into a three-dimensional network structure of carbonaceous. Keeping the heat for 2 hours can allow the first conductive agent to fully undergo a carbonization reaction at 800°C. At this temperature, most of the organic components inside the material have been decomposed, and the remaining components are mainly carbonaceous components. The heat preservation process can give carbon atoms enough time to rearrange more fully, making the carbonaceous structure more regular and stable. For example, for phenolic foam, the chemical bonds between the benzene ring structures will be further adjusted at this temperature to form a carbon layer structure that is more conducive to electron conduction. The heat preservation at this stage can also further develop the pore structure inside the material, providing a better structural basis for subsequent ball milling and mixing with the second conductive agent, because a good pore structure helps to increase the specific surface area of ​​the material and the contact area with other conductive agents. The temperature is increased from 800°C to 950°C at a heating rate of 10°C / min. This stage is to further increase the degree of carbonization. After the first stage of carbonization and heat preservation, the material has formed a certain carbonaceous structure, but there may still be some incompletely carbonized areas or structural defects. Heating again can allow these areas to continue the carbonization reaction and further convert the remaining organic components into carbonaceous components. At the same time, as the temperature increases, the activity of carbon atoms will be further enhanced, which is conducive to the diffusion and rearrangement of carbon atoms inside the material, making the carbonaceous structure more dense and orderly. For example, for materials such as melamine foam, this stage can make impurity elements such as nitrogen atoms in the material further volatilize or form more stable chemical bonds with carbon, further purify the carbonaceous structure, and improve its conductivity.Moreover, higher temperatures help to form some active sites on the material surface that are beneficial to the subsequent ozonation reaction, such as some unsaturated carbon-carbon bonds or carbon-heteroatom bonds. These active sites can react better with ozone during the ozonation process, thereby optimizing the performance of the first conductive agent.

[0050] In step S2, ball milling can reduce the particle size of the carbonized first conductive agent and increase its specific surface area. After the specific surface area is increased, the first conductive agent can have more active sites to participate in subsequent reactions or conductive processes. At the same time, ball milling can also improve the crystal structure of the material, reduce crystal defects, and further improve the conductivity of the material.

[0051] Specifically, in this embodiment, the carbonized first conductive agent is placed in a ball mill and ball milled at a rotation speed of 100-200 rpm for 10-20 min. Ball milling at a low rotation speed of 100-200 rpm can prevent the main structure of the first conductive agent from being damaged.

[0052] In step S3, ozone is a strong oxidant that can react with unsaturated bonds or active sites on the surface of the first conductive agent. In this process, ozone molecules will add to active structures such as carbon-carbon double bonds on the surface of the material, introduce oxygen functional groups such as carbonyl and carboxyl, and form an ozonated first conductive agent. The introduction of these oxygen functional groups can change the surface properties of the first conductive agent, such as increasing the affinity of the first conductive agent for the positive electrode active material, making it easier to interact with the second conductive agent, and even in the case of a small amount of conductive agent, it can improve battery performance and also improve the dispersibility of the material.

[0053] Specifically, the mass concentration of ozone is 5-15ug / L, the gas flow rate is 0.8-1.2L / min, and the reaction time is 10-15min. Controlling the above reaction conditions can obtain an appropriate amount of functional groups. Too few functional groups cannot prevent the agglomeration of the first conductive agent, and too many functional groups will cause the conductivity of the ozonated first conductive agent to decrease.

[0054] In step S4, mixing enables the two conductive agents to fully contact and use mechanical force to evenly disperse them together. In this process, due to the possible interaction between the oxygen functional groups on the surface of the ozonated first conductive agent and the second conductive agent, such as van der Waals force, hydrogen bonding or chemical bonding (in some cases), a tight conductive network can be formed to prepare a composite conductive agent. By fully mixing the two conductive agents, a composite conductive agent with a synergistic effect is formed. The second conductive agent itself has good conductivity, and after mixing with the treated first conductive agent, it can make up for each other's shortcomings.

[0055] In this embodiment, the first conductive agent is treated by carbonization, ball milling, ozonation, etc., and then mixed with the second conductive agent to form an interwoven conductive network. This network structure can provide more electron conduction paths, and can more effectively transmit electrons and reduce resistance compared to a single conductive agent, thereby improving the charge and discharge efficiency of electrochemical devices such as batteries. Among them, the carbonization process removes the unstable components in the first conductive agent, and after ball milling and ozonation, the structure of the composite conductive agent is more stable. During the long-term use of the battery, the stable conductive agent can maintain its conductive properties and reduce the battery performance degradation caused by changes in the conductive agent structure or decomposition. For example, during the charge and discharge cycle of the battery, the stable conductive agent can better adapt to the volume change of the electrode material and maintain the conductivity of the electrode. Ozone has strong oxidizing properties and can react with unsaturated functional groups in the first conductive agent, such as unsaturated bonds such as carbon-nitrogen double bonds. During the ozonation process, the unsaturated bonds are broken, and the oxygen atoms will combine with the broken molecular fragments, thereby introducing functional groups such as carboxyl and hydroxyl groups into the first conductive agent. Both carboxyl and hydroxyl are polar functional groups. After the introduction of the first conductive agent, the surface polarity of the first conductive agent is enhanced, so that the polar interaction between the first conductive agent and the second conductive agent is enhanced, thereby improving the contact condition between the two and improving the compatibility. Similarly, the compatibility of the composite conductive agent and the positive electrode active material is also improved. By introducing polar functional groups, they can also attract each other with the active material, increase the contact area, and thus improve the conductivity. Good compatibility enables the two conductive agents to work better together and be evenly dispersed in the electrode material. This not only helps to improve the conductivity, but also improves the overall structural uniformity of the electrode material, prevents the local performance of the electrode from deteriorating due to problems such as conductive agent agglomeration, thereby improving the cycle life and safety of the battery.

[0056] In one embodiment, the first conductive agent is one or more combinations of melamine foam, polyurethane foam and phenolic foam. The second conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene.

[0057] In the present embodiment, melamine foam is a material with a three-dimensional mesh structure. It is made by the polycondensation reaction of melamine and formaldehyde, and this structure makes it have a high porosity and can provide a large specific surface area. After being treated by carbonization, the pore structure inside it can provide a channel for electron transmission. Moreover, the melamine foam itself is light in weight, and the overall weight can be reduced in the composite conductive agent. Polyurethane foam has good elasticity and flexibility. It is generated by the reaction of polyols and isocyanates, and the molecular structure of this material can be adjusted by changing the ratio of raw materials. In the preparation process of the conductive agent, its elasticity helps to maintain a certain structural integrity during mechanical treatments such as ball milling. At the same time, the high porosity also enables it to form a structure that is conducive to electron conduction after carbonization. For example, in battery electrodes, it can better adapt to the volume change of electrode materials during charging and discharging. Phenolic foam is made by foaming phenolic resin, which has excellent thermal stability and chemical stability. During the high-temperature carbonization process, phenolic foam can maintain its shape well, and because its molecular structure contains a large number of benzene ring structures, it may form a more regular carbon structure after carbonization, which is conducive to electron conduction. Its chemical stability also enables it to resist chemical corrosion in subsequent chemical treatment processes such as ozonation and in the battery use environment, ensuring the stable performance of the composite conductive agent.

[0058] In the above embodiment, conductive carbon black is an amorphous carbon material with a very high specific surface area. Its particles are very fine and can form a large number of conductive contact points in the composite conductive agent. After mixing with the treated first conductive agent, it can be filled in the pores or surface of the first conductive agent to enhance the connectivity of the conductive network. At the same time, the production cost of conductive carbon black is relatively low and its source is wide, which makes it cost-effective in the large-scale production of composite conductive agents. Conductive graphite has a typical layered crystal structure, which enables electrons to conduct quickly between layers. In the composite conductive agent, conductive graphite can cooperate with other conductive agents to provide efficient electron transmission channels using its own layered structure. For example, in a battery electrode, when the volume of the electrode material changes, the layered structure of the conductive graphite can maintain the conductive properties to a certain extent and reduce the increase in resistance caused by structural changes. Carbon fiber is a fibrous carbon material with the characteristics of high strength and high modulus. In the composite conductive agent, carbon fiber can play a dual role of reinforcement and conductivity. It can connect different conductive particles like a "bridge" to form a long-range conductive path. Moreover, the high strength of carbon fiber helps to improve the mechanical stability of the composite conductive agent in the electrode material and prevent the structural damage of the conductive agent during electrode preparation or battery use. Carbon nanotubes have a unique one-dimensional nanostructure and are divided into single-walled carbon nanotubes and multi-walled carbon nanotubes. They have an extremely high aspect ratio, and the transmission of electrons in carbon nanotubes is almost unaffected by scattering, so they have excellent electrical properties. In the composite conductive agent, carbon nanotubes can be interspersed between other conductive agents to build a three-dimensional conductive network. Its nanometer-sized tube diameter also allows it to penetrate into the microstructure of the electrode material, effectively improving the local conductivity of the electrode. Graphene is a carbon atom composed of sp 2 Hybrid orbitals form a two-dimensional carbon nanomaterial with a hexagonal honeycomb lattice. It has extremely high carrier mobility, and electrons can move quickly within the graphene plane. In the composite conductive agent, graphene can be laid flat on the surface of the first conductive agent or stacked with other conductive agents to form a continuous conductive plane. At the same time, the high specific surface area of ​​graphene also helps to interact with other conductive agents and enhance the overall conductive properties of the composite conductive agent.

[0059] In one embodiment, the first conductive agent accounts for 2% to 10% of the composite conductive agent by weight.

[0060] In this embodiment, the first conductive agent forms a special conductive structure after complex treatments such as carbonization, ball milling and ozonation. The first conductive agent at this ratio can serve as a part of the "skeleton" of the conductive network and cooperate with the second conductive agent. Even at a lower content, its treated structure (such as a carbonaceous structure with a certain porosity) can provide additional channels for electron conduction and help improve the overall structural stability of the composite conductive agent.

[0061] For example, in battery electrode applications, a small amount of the first conductive agent can help maintain the structural integrity of the electrode during the charge and discharge process and prevent the conductive path from breaking due to volume changes in the electrode material. At the same time, its unique structure can adsorb some second conductive agents, such as conductive carbon black or carbon nanotubes, so that they are better dispersed, thereby indirectly improving the conductive performance. At the same time, the preparation process of the composite conductive agent is relatively complicated, including steps such as carbonization, ball milling and ozonation of the first conductive agent. If the content of the first conductive agent is too high, the production cost of the entire composite conductive agent and the complexity of the preparation process will increase. Maintaining a low ratio of 2% can effectively control the cost and process difficulty while ensuring a certain performance improvement. A higher ratio of the first conductive agent may face problems of dispersion and uniformity when ball milling with the second conductive agent. Although the first conductive agent has a certain activity after treatment, it is prone to agglomeration at a high ratio due to its own structural characteristics (such as high porosity or large particles). This will cause the local conductive properties of the composite conductive agent to differ too much, affecting the overall performance. Maintaining a ratio below 10% helps ensure that the two conductive agents can form a uniform conductive network during ball milling and give full play to their respective advantages. At the same time, a higher proportion of the first conductive agent will face problems of dispersion and uniformity when ball-milling with the second conductive agent. Although the first conductive agent has a certain activity after treatment, it is prone to agglomeration at a high proportion due to its own structural characteristics (such as high porosity or large particles). This will cause the local conductive properties of the composite conductive agent to differ too much, affecting the overall performance. Keeping the ratio below 10% helps ensure that the two conductive agents can form a uniform conductive network during the ball milling process and give full play to their respective advantages.

[0062] In one embodiment, the particle size of the first conductive agent is 2 micrometers to 5 micrometers, and the particle size of the second conductive agent is 40 nanometers to 60 nanometers.

[0063] In this embodiment, the particle size of the first conductive agent is in the range of 2 microns to 5 microns, which can provide a good macroscopic conductive path. Its larger particle size relative to the second conductive agent helps to form a "skeleton" structure in the composite conductive agent system. The first conductive agent after carbonization, ball milling and other treatments has a rich pore structure within this particle size range. It can provide a holding space for the second conductive agent with a smaller particle size, so that the second conductive agent can be better filled therein, thereby enhancing the interaction between the two conductive agents. The smaller particle size allows the second conductive agent to penetrate into the pores and surface microstructures of the first conductive agent. At the nanoscale, the second conductive agent can take advantage of its small size to fill the tiny gaps between the first conductive agent particles and form a denser conductive network. At the same time, the nanoparticle size of the second conductive agent is conducive to its uniform dispersion around the first conductive agent. Nanoparticles have a large specific surface area and surface energy, making them easier to adsorb on the surface of the first conductive agent or fill in its pores when ball-milled and mixed with the first conductive agent. This close combination improves the stability of the composite conductive agent and reduces the possibility of agglomeration or sedimentation of the conductive agent during the preparation of the electrode material or the use of the battery.

[0064] In one embodiment, the inert gas is one or more of nitrogen, argon and neon.

[0065] In this embodiment, nitrogen is a gas with relatively stable chemical properties. Its molecules are composed of two nitrogen atoms bonded by a triple bond (N≡N), and this chemical bond is very strong, making it difficult for nitrogen to be decomposed or participate in the reaction under general chemical reaction conditions. During the carbonization process, nitrogen can effectively isolate oxygen in the air and prevent the first conductive agent from being oxidized. Because if the first conductive agent (such as melamine foam, polyurethane foam, phenolic foam) is in contact with oxygen at high temperature, combustion or oxidation reaction will occur, resulting in the destruction of the material structure, and it is impossible to form an ideal carbonaceous structure for subsequent conductive agent preparation. Argon is a rare gas, and its outermost electron layer has reached a stable eight-electron structure. This makes argon have extremely high chemical stability and almost no chemical reaction with other substances. Using argon as an inert gas in the carbonization process can provide a very pure oxygen-free environment for the first conductive agent. This stable environment helps to accurately control the process of the carbonization reaction, ensure that the first conductive agent can be pyrolyzed and the carbon structure rearranged in the expected manner, and is conducive to the formation of high-quality carbonized first conductive agent. Neon is also a rare gas with stable chemical properties. Similar to argon, it can provide a stable, oxygen-free atmosphere for the carbonization reaction. However, neon is relatively rarely used alone in practical applications, and is more often used in combination with nitrogen or argon, mainly because of its relatively high cost. However, in some special cases where the reaction environment is extremely demanding, the use of neon can further improve the stability and accuracy of the reaction. In actual operation, one or more combinations of nitrogen, argon and neon are used, which can be selected according to specific needs and cost considerations. Nitrogen has a relatively low cost and can be used as the main inert gas when the reaction environment is not particularly demanding. When higher chemical stability or more precise reaction control is required, argon or neon can be appropriately added. For example, when preparing high-purity, high-performance composite conductive agents, a combination of nitrogen and argon may be used, which takes into account both cost and ensures reaction stability and product quality. At the same time, by changing the ratio of the gas combination, the environment of the carbonization reaction can be flexibly adjusted.

[0066] In one embodiment, before the step of carbonizing the first conductive agent in an inert gas atmosphere to obtain the carbonized first conductive agent, the step further includes: acid washing, water washing and drying the first conductive agent.

[0067] In this embodiment, the first conductive agent (such as melamine foam, polyurethane foam, phenolic foam) may adsorb or contain some metal ion impurities, unreacted chemical reagents, etc. during production or storage. Pickling can effectively dissolve and remove these impurities. For example, for a first conductive agent containing a small amount of metal oxide impurities, a suitable acid (such as dilute hydrochloric acid, dilute sulfuric acid, etc.) can be used to cause a chemical reaction to convert the metal oxide into a soluble metal salt, and then remove these impurities through a subsequent water washing step. Pickling can also remove some functional groups on the surface of the first conductive agent that may affect the carbonization process. For example, there may be some easily oxidized groups on the surface, which may cause unnecessary side reactions during the carbonization process. Pickling can clean them up, so that the carbonization process is more smoothly carried out in the direction of forming an ideal carbonaceous structure. The surface of the first conductive agent can be roughened to a certain extent by pickling. For example, the acid reacts chemically with the surface of the material, which will break some chemical bonds on the surface and form tiny pits or protrusions, which is conducive to the rearrangement of carbon atoms and the growth of carbonaceous structures in the subsequent carbonization process. Moreover, the surface after pickling may carry some acidic functional groups (such as carboxyl groups), which may have a positive effect on the formation and properties of the carbonaceous structure in the subsequent carbonization process, such as affecting the deposition mode of carbon atoms or the growth direction of the carbon layer. Water washing is to completely wash away the soluble impurities (such as metal salts, acid, etc.) generated during the pickling process. If these impurities remain in the first conductive agent, local defects in the material or the formation of new impurity phases may occur during the carbonization process. For example, the residual metal salts may decompose and react with carbon during high-temperature carbonization, changing the properties of the carbonaceous structure, or forming an uneven distribution of components in the material, affecting the performance of the final composite conductive agent. Water washing can also adjust the pH of the first conductive agent. After pickling, the surface of the material may be acidic, and water washing can restore it to a state close to neutrality to avoid unnecessary chemical reactions caused by the acidic environment during the subsequent drying and carbonization process. If the first conductive agent contains water, the water will evaporate at high temperature during the carbonization process. This process may cause vapor pressure inside the material, causing cracks in the material, destruction of the pore structure, etc. Moreover, the presence of moisture may cause side reactions such as hydrolysis in the early stage of carbonization, interfering with the normal pyrolysis and carbon structure formation process. Through drying treatment, the moisture in the first conductive agent can be removed to ensure that the carbonization process can be carried out under relatively stable conditions, which is conducive to the formation of a uniform, high-quality carbonized first conductive agent. The dried first conductive agent is easier to handle during subsequent carbonization, ball milling and other operations. For example, when the dried material is placed in carbonization equipment such as a tubular furnace, it will not show adhesion, agglomeration and other phenomena due to the presence of moisture, which can better ensure the uniformity and repeatability of the reaction.Moreover, the weight and composition of the dried material are more stable, which is conducive to accurately controlling the process parameters during the carbonization process, such as heating rate, holding time, etc., so as to better control the quality of the first conductive agent after carbonization.

[0068] In the above embodiment, specifically, hydrochloric acid pickling is adopted, and the operation steps are to immerse and clean the first conductive agent in hydrochloric acid, wash it with deionized water and alcohol, and dry it by drying or air drying.

[0069] An embodiment of the present invention provides a composite conductive agent, which is prepared by any of the methods described above.

[0070] In this embodiment, the composite conductive agent includes a first conductive agent and a second conductive agent, which are prepared by the above method. After the first conductive agent is treated by carbonization, a good conductive network is formed by itself, and then compounded with the second conductive agent. The two work together to effectively improve the overall conductive performance of the composite conductive agent.

[0071] An embodiment of the present invention provides a positive electrode plate, which includes a current collector and a positive electrode material, and the positive electrode material includes the above-mentioned composite conductive agent, a positive electrode active material and a binder.

[0072] In this embodiment, the current collector plays a key role in collecting and conducting current in the positive electrode sheet. It can be a metal material with good conductivity, such as aluminum foil. During the operation of the battery, the current generated by the electrode reaction is conducted to the current collector through the positive electrode material, and then output through the external circuit. The current collector is in close contact with the positive electrode material, providing an efficient channel for the transmission of electrons, ensuring that the battery can stably supply power to the outside. The main function of the composite conductive agent in the positive electrode material is to enhance conductivity. The composite conductive agent prepared by the above method, the conductive network formed by the first conductive agent and the second conductive agent can effectively reduce the internal resistance of the positive electrode material. Between the particles of the positive active material, the composite conductive agent can fill the gap and provide more conduction paths for electrons. For example, during the charge and discharge process of the battery, when the positive active material undergoes a redox reaction, the generated electrons can be quickly transmitted between the active material particles through the composite conductive agent, thereby improving the charge and discharge efficiency of the battery. The positive active material is the core component of the redox reaction in the battery. Such as lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium cobalt oxide, these materials receive electrons from the external circuit during charging, undergo reduction reactions, and store electrical energy; during discharge, they release electrons, undergo oxidation reactions, and provide electrical energy to the external circuit. The performance of the positive electrode active material directly determines the key electrochemical performance indicators of the battery, such as capacity and voltage. It works closely with the composite conductive agent, and on the basis of providing a good conductive environment for the composite conductive agent, it exerts its electrochemical activity to realize the energy storage and release functions of the battery. The role of the binder is to bind the positive electrode active material and the composite conductive agent together so that the positive electrode material forms a whole. It can prevent the positive electrode active material and the composite conductive agent from falling off or being unevenly dispersed during the processing of the battery (such as rolling, slicing, etc.) and during use. For example, binders such as polyvinylidene fluoride can form a viscous network in the positive electrode material, firmly fix the active material particles and conductive agent particles on the surface of the current collector, ensure the integrity and stability of the electrode structure, and thus ensure the performance and service life of the battery.

[0073] In the above embodiments, the addition of the composite conductive agent effectively improves the conductivity of the positive electrode material and reduces the polarization phenomenon of the battery during the charge and discharge process. The positive electrode active material can exert its electrochemical properties in a better conductive environment, thereby improving the charge and discharge efficiency, capacity retention rate and rate performance of the battery. For example, during high-rate charge and discharge, a good conductive network can enable the battery to receive and release electrical energy faster and reduce energy loss.

[0074] In one embodiment, the positive electrode active material is one or more combinations of lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium cobalt oxide.

[0075] In this embodiment, lithium iron phosphate has a stable olivine structure, and its structure changes little during the charging and discharging process. This structural characteristic makes it safer during the use of the battery. Even under extreme conditions such as high temperature and overcharging, it is not easy to have dangerous situations such as thermal runaway. At the same time, the raw materials of lithium iron phosphate are widely available and the price is relatively stable. Its main components, iron and phosphorus, are abundant in nature, which makes the production cost of lithium iron phosphate relatively low, which is conducive to large-scale production and application. Nickel cobalt manganese oxide can achieve a higher energy density by adjusting the ratio of the three elements of nickel (Ni), cobalt (Co), and manganese (Mn). This high energy density characteristic enables batteries using nickel cobalt manganese oxide as the positive active material to store more electrical energy in a smaller volume or weight; at the same time, nickel cobalt manganese oxide has good electronic and ion conductivity, which enables the battery to quickly undergo redox reactions during high-rate charging and discharging. In some application scenarios that require fast charging or high power output, such as fast charging of power tools and acceleration of high-performance electric vehicles, nickel cobalt manganese oxide can play its advantages and provide better performance. Lithium cobalt oxide has a high energy density and can provide a higher voltage platform for the battery, so that the battery can output higher energy during the discharge process. At the same time, the electrochemical performance of lithium cobalt oxide is stable. Under normal charging and discharging conditions, it can maintain good performance and provide reliable power output for the battery. Using lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium cobalt oxide as positive electrode active materials in one or more combinations can make full use of their respective advantages and make up for each other's shortcomings. For example, the combination of lithium iron phosphate and lithium nickel cobalt manganese oxide can improve the energy density and rate performance of the battery while ensuring a certain safety and cycle life.

[0076] In one embodiment, by weight, the positive electrode active material accounts for 94% to 98% of the positive electrode material, the composite conductive agent accounts for 1% to 3% of the positive electrode material, and the binder accounts for 1% to 3% of the positive electrode material.

[0077] In this embodiment, the positive electrode active material is the core part of the battery where the redox reaction occurs, and its high proportion is to ensure that the battery can store enough electrical energy. Within the above-mentioned ratio range, the battery can utilize the electrochemical properties of the positive electrode active material, such as the electron gain and loss of materials such as lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium cobalt oxide during the charging and discharging process to achieve energy storage and release. A higher ratio can ensure that the battery has enough capacity to meet the needs of various application scenarios. For example, in electric vehicles, sufficient positive electrode active materials can provide enough power to support the vehicle to travel a sufficient mileage; since the properties of the positive electrode active material directly determine the key electrochemical properties of the battery such as voltage and energy density, maintaining a high ratio can make the electrochemical properties of the battery mainly dominated by the positive electrode active material. The main function of the composite conductive agent is to improve the conductivity of the positive electrode material. At this relatively low ratio, it can form a conductive path between the positive electrode active material particles and reduce the resistance to electron transmission. For example, when the composite conductive agent is evenly distributed between the positive electrode active material particles, during the battery charging and discharging process, electrons can be quickly conducted between the active material particles through the composite conductive agent, thereby improving the battery's charge and discharge efficiency and rate performance. Although the proportion is low, it is enough to significantly improve the conductivity of the positive electrode material. Keeping the composite conductive agent at a low proportion can avoid excessive interference with other properties of the positive electrode material. If the proportion of the composite conductive agent is too high, it may affect the structural stability of the positive electrode material or change other physical and chemical properties of the positive electrode material, such as density, porosity, etc. In the range of 1%-3%, it can effectively improve the conductivity while ensuring that the main properties of the positive electrode material are still synergistically maintained by the positive electrode active material and the binder. The role of the binder is to bind the positive electrode active material and the composite conductive agent together to form a stable positive electrode material structure. In the proportion range of 1%-3%, the binder can give full play to its bonding effect to prevent the positive electrode active material and the composite conductive agent from falling off or unevenly dispersing during the processing of the battery (such as rolling, slicing, etc.) and the use of the battery. This is crucial to ensure the structural integrity and stability of the positive electrode material. For example, during the long-term use of the battery, a stable positive electrode material structure can reduce the degradation of battery performance caused by material shedding or uneven distribution.

[0078] In one embodiment, the binder is one or more combinations of methyl methacrylate, polyacrylonitrile, polyoxypropylene, polyoxyethylene, polyvinyl chloride, polyvinylidene fluoride and polytetrafluoroethylene.

[0079] In the above embodiment, methyl methacrylate has good bonding properties as a binder. It can form a strong bonding force between the positive electrode active material and the composite conductive agent, making the positive electrode material structure compact. This is because its molecular chain contains polar groups, which can interact with the active material in the positive electrode material and the functional groups on the surface of the conductive agent, such as hydrogen bonds or van der Waals forces. Polyacrylonitrile is a polymer material with high strength and toughness. As a binder, it can provide good mechanical stability for the positive electrode material. In the processing process of the battery (such as rolling, slicing, etc.), it can withstand a certain mechanical pressure to prevent the positive electrode material from cracking or stratification, and has good chemical stability and can resist the erosion of some common chemical substances. In the electrolyte environment of the battery, the polyacrylonitrile binder can maintain the integrity of its own structure and ensure that the bonding effect of the positive electrode material is not affected by the electrolyte. Polyoxypropylene has good flexibility and elasticity. This property enables it to adapt to the stress caused by the volume change of the positive electrode material during the charging and discharging process of the battery. Especially during high-rate charge and discharge, the volume change of the positive electrode active material is large. The polyoxypropylene binder can alleviate the impact of this volume change through its own elastic deformation, thereby maintaining the structural integrity of the positive electrode material, and has good solubility. In the preparation process of some binders, it can be easily mixed with other ingredients, which is conducive to the preparation of a uniform binder solution, thereby better bonding the positive electrode material. Polyoxyethylene is a hydrophilic polymer material, which has advantages in some battery systems containing aqueous components or in application scenarios that are sensitive to humidity. It can form hydrogen bonds with water molecules, which helps to maintain the humidity balance of the internal environment of the battery. At the same time, it can also improve the wettability of the positive electrode material to a certain extent, so that the electrolyte can better contact the positive electrode material. Polyvinyl chloride is a relatively low-priced and widely available polymer material. As a binder, it can reduce the production cost of the battery to a certain extent. At the same time, it has good chemical corrosion resistance, can maintain stable performance in the electrolyte environment of the battery, and ensure the bonding effect of the positive electrode material. Polyvinylidene fluoride is a binder widely used in the field of lithium-ion batteries. It has excellent chemical stability and can maintain good performance in various electrolyte environments (such as organic electrolytes). During the long-term use of the battery, the polyvinylidene fluoride binder can effectively prevent the chemical reaction between the positive electrode material and the electrolyte, ensuring the safety and stability of the battery. Polytetrafluoroethylene has excellent chemical stability and corrosion resistance, and can resist the erosion of almost all chemicals. It can maintain good performance in the complex electrolyte environment of the battery and various working conditions. It also has an extremely low friction coefficient, which may be an advantage in some special battery designs (such as flexible batteries) to reduce the internal friction of the battery during bending or deformation. At the same time, by selecting a combination of different binders, their respective advantages can be fully utilized and make up for each other's shortcomings.For example, the combination of polyvinylidene fluoride and polyoxypropylene can ensure good bonding performance and chemical stability while using the elasticity of polyoxypropylene to adapt to the volume change of the positive electrode material. According to the specific application scenario and performance requirements of the battery, the combination and proportion of the binder can be flexibly adjusted. For example, for batteries that need to work in a high temperature environment, the proportion of polytetrafluoroethylene can be increased to improve the high temperature resistance of the battery; for batteries that require good flexibility and processing performance, the proportion of polyoxyethylene can be increased. It can better meet the needs of different battery applications.

[0080] An embodiment of the present invention provides a method for preparing a positive electrode sheet, which is used to prepare the positive electrode sheet as described in any one of the above items, comprising the following steps:

[0081] S1, mixing the positive electrode active material and the composite conductive agent uniformly to obtain a mixture;

[0082] S2, adding a binder to the mixture to perform fiberization to obtain a fiberized mixture;

[0083] S3, banburying the fiberized mixture to obtain a banburyed fiberized mixture;

[0084] S4, rolling the fiberized mixture after the banburying to obtain a positive electrode film;

[0085] S5. Compounding the positive electrode film with the carbon-coated aluminum foil to obtain the positive electrode plate.

[0086] In step S1, the fiberizer can effectively stir and disperse the materials, so that the particles of the positive electrode active material and the composite conductive agent are fully contacted and mixed in three-dimensional space. The positive electrode active material (such as lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, etc.) is the core part of the electrochemical performance of the battery, and the composite conductive agent is mainly used to improve the conductivity of the positive electrode material. By fully mixing in the fiberizer, it can be ensured that the composite conductive agent is evenly distributed between the particles of the positive electrode active material, so that during the battery charging and discharging process, electrons can be quickly and evenly conducted between the positive electrode active materials. The fiberized mixture is an intermediate product in the preparation process of the positive electrode sheet. After this mixing process, the state of the material begins to show a structural feature similar to fiber interweaving. From a microscopic point of view, the particles of the positive electrode active material and the composite conductive agent are connected together by a binder, just like fibers interweaving with each other. This structure is conducive to the further fusion and molding of the material in the subsequent mixing step, and can ensure that the components of the material will not be easily separated in the subsequent processing process (such as mixing and rolling), and maintain good uniformity. In the fiberizer, the positive electrode active material and the composite conductive agent are fully mixed. The fiberizer uses its mechanical stirring and dispersing effect to evenly distribute the two components at the microscopic level. During this process, the composite conductive agent will be interspersed between the positive electrode active material particles to form a preliminary conductive network foundation.

[0087] In step S2, after obtaining the mixture of the positive electrode active material and the composite conductive agent, a binder is added in order to further integrate the previous mixture by utilizing the bonding properties of the binder. The binder (such as methyl methacrylate, polyvinylidene fluoride, etc.) can form a sticky film on the surface of the particles of the positive electrode active material and the composite conductive agent, and bond them together by physical adsorption or chemical action. In this step, the binder is evenly wrapped on the surface of the particles of the positive electrode active material and the composite conductive agent to form a stable fibrous mixture.

[0088] In step S3, banburying is a process of vigorously mixing and kneading the fiberized mixture in a closed environment. In the banbury mixer, the material is repeatedly sheared, extruded and stirred by a pair of rotors rotating in opposite directions. This process can make the various components in the fiberized mixture (positive electrode active material, composite conductive agent and binder) more closely combined. The high shear force generated during the banburying process can further break up the agglomerates that may exist between the material particles, making the mixing of the materials more uniform and delicate. Banburying helps to improve the microstructure of the positive electrode material. After banburying, the contact between the particles in the positive electrode material is closer, forming a more continuous conductive network and bonding network. For example, during the battery charging and discharging process, the tight structure can better resist the volume change of the positive electrode material caused by chemical reactions, reduce electrode polarization, and improve the battery charging and discharging efficiency. At the same time, the material after banburying has better plasticity, providing a more suitable material state for the subsequent rolling step.

[0089] In step S4, the positive electrode film obtained by rolling has better flatness and uniform thickness, which is very important for the performance and safety of the battery. The flat film can ensure better contact with the carbon-coated aluminum foil (current collector), reduce contact resistance, and improve the overall conductivity of the battery. At the same time, the uniform thickness can ensure uniform current distribution during the charge and discharge process of the battery, avoiding safety hazards caused by excessive local current, such as overheating and short circuit.

[0090] In step S5, the carbon-coated aluminum foil is used as a current collector. Its main function is to collect and conduct the current generated during the operation of the battery. After being compounded with the positive electrode film, the current in the positive electrode material can be effectively exported to the external circuit, and the current of the external circuit can also be evenly distributed to the positive electrode material. This tight composite structure can ensure the smooth conduction of the current during the charge and discharge process of the battery and improve the overall performance of the battery.

[0091] Furthermore, the positive electrode film and the carbon-coated aluminum foil are pressed together at a temperature of 80 degrees Celsius to obtain the positive electrode plate.

[0092] In this embodiment, the physical properties of the binder (such as methyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, etc.) used in the preparation process of the positive electrode sheet will change at different temperatures. The temperature of 80 degrees Celsius is a temperature point that can make the binder reach a better softening or flow state. For example, the polyvinylidene fluoride binder is relatively hard and has limited viscosity at room temperature, but at 80 degrees Celsius, it can be softened appropriately, so that the small gap between the positive electrode film and the carbon-coated aluminum foil can be better filled. When the binder is in this suitable softened state, it can more effectively play a bonding role and enhance the tightness of the connection between the positive electrode film and the carbon-coated aluminum foil. The temperature of 80 degrees Celsius will not be too high to cause the positive active material (such as lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, etc.) and composite conductive agent in the positive electrode film. The composition will not be too low so that the binder cannot effectively play the bonding function. For the carbon-coated aluminum foil, this temperature is also within the normal operating temperature range that it can withstand, and will not cause deformation or other adverse effects of the aluminum foil. In this way, a good combination of materials can be achieved while ensuring the stability of their own performance. At the same time, by pressing at 80 degrees Celsius, a closer contact can be formed between the positive electrode film and the carbon-coated aluminum foil. The binder fully functions at this temperature, filling the gap between the two, so that the interfacial bonding force between them is significantly enhanced. This close bonding can effectively reduce the interface resistance, because when the interface is tightly bonded, the obstacles encountered by electrons when transmitting between the positive electrode film and the carbon-coated aluminum foil will be reduced, thereby improving the conductivity efficiency of the battery.

[0093] A fifth aspect of the present invention provides a battery, comprising a positive electrode sheet as described in any one of the above items.

[0094] In this embodiment, the battery further includes a negative electrode plate and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode active material in the positive electrode plate participates in the positive electrode reaction and can reversibly extract and embed the first metal ion. Specifically, the first metal ion is selected from lithium ions, sodium ions or magnesium ions.

[0095] The preparation process and performance of the present invention are described below with reference to some specific embodiments.

[0096] In the following examples and comparative examples, hydrochloric acid is derived from Aladdin reagent; melamine foam, polyurethane foam and phenolic foam are all derived from Shanghai Beiyou Building Materials Co., Ltd., and alcohol is derived from Xilong Science Co., Ltd. In NCM613, N represents nickel, C represents cobalt, and M represents manganese. 613 represents that the atomic ratio of nickel, cobalt and manganese is about 6:1:3.

[0097] Embodiment 1:

[0098] Preparation of composite conductive agent:

[0099] S0, 10g of melamine foam was soaked in 2mol / l hydrochloric acid, and then the melamine foam was rinsed with deionized water and alcohol respectively, and after drying with a hot air blower or an oven, the melamine foam was placed in a quartz crucible;

[0100] S1. Place a quartz crucible into a tubular furnace and introduce nitrogen. Heat the temperature to 800°C at a heating rate of 10°C / min, keep the temperature constant for 2 hours, then heat the temperature from 800°C to 950°C at a heating rate of 10°C / min, keep the temperature constant for 6 hours, and obtain carbonized melamine foam.

[0101] S2, placing the carbonized melamine foam into a ball mill, and ball milling at a speed of 100-200 rpm for 10-20 min to obtain a ball-milled melamine foam;

[0102] S3, putting the ball-milled melamine foam into a glass tube, introducing ozone gas with a mass concentration of 15ug / l at a rate of 1.2L / min, reacting for 10-15min to obtain ozonated melamine foam;

[0103] S4. Add ozonized melamine foam with a particle size of 5 um and 2.73 g of conductive carbon black with a particle size of 60 nm into a planetary mixer according to a weight ratio of 10% of the composite conductive agent, and mix at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0104] Preparation of positive electrode sheet (dry preparation):

[0105] S1, adding 96.5wt% of lithium nickel cobalt manganese oxide NCM613 and 2wt% of a composite conductive agent into a fiberizer, and mixing at a speed of 200 rpm for 6 minutes to obtain a mixture;

[0106] S2, continue to add 1.5wt% polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture;

[0107] S3, placing the fiberized mixture in an internal mixer and mixing it at a temperature to obtain a fiberized mixture after mixing;

[0108] S4, placing the fiberized mixture after banburying on a rolling machine for rolling to obtain a positive electrode film;

[0109] S5. At a temperature of 80° C., press the positive electrode film and the current collector to obtain a positive electrode sheet.

[0110] Embodiment 2:

[0111] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 5 um is added to a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73 g of conductive carbon black with a particle size of 60 nm, and mixed at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0112] Embodiment 3:

[0113] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 5 um is added to a planetary mixer according to 2% of the weight ratio of the composite conductive agent and 2.73g of conductive carbon black with a particle size of 60nm, and mixed at a speed of 500rmp / min for 15 minutes to obtain a composite conductive agent.

[0114] Embodiment 4:

[0115] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 5 um is added to a planetary mixer according to 1% of the weight ratio of the composite conductive agent and 2.73g of conductive carbon black with a particle size of 60nm, and mixed at a speed of 500rmp / min for 15 minutes to obtain a composite conductive agent.

[0116] Embodiment 5:

[0117] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 5 um is added to a planetary mixer according to 20% of the weight ratio of the composite conductive agent and 2.73g of conductive carbon black with a particle size of 60nm, and mixed at a speed of 500rmp / min for 15 minutes to obtain a composite conductive agent.

[0118] Embodiment 6:

[0119] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 3.5um is added to a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73g of conductive carbon black with a particle size of 50nm, and mixed at a speed of 500rmp / min for 15min to obtain a composite conductive agent.

[0120] Embodiment 7:

[0121] In this embodiment, compared with Example 1, the only difference is that the ozonated melamine foam with a particle size of 2 um is added to a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73g of conductive carbon black with a particle size of 40nm, and mixed at a speed of 500rmp / min for 15 minutes to obtain a composite conductive agent.

[0122] Embodiment 8:

[0123] In this embodiment, compared with embodiment 1, the difference is that the ball-milled melamine foam is placed in a glass tube, and ozone gas with a mass concentration of 10ug / l is introduced at a rate of 1.0l / min, and the reaction is carried out for 10-15min to obtain ozonized melamine foam;

[0124] The ozonated melamine foam with a particle size of 2 um was added into a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73 g of conductive carbon black with a particle size of 40 nm, and mixed at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0125] Embodiment 9:

[0126] In this embodiment, compared with embodiment 1, the difference is that the ball-milled melamine foam is placed in a glass tube, and ozone gas with a mass concentration of 5 ug / l is introduced at a rate of 0.8 l / min, and the reaction is carried out for 10-15 minutes to obtain ozonized melamine foam;

[0127] The ozonated melamine foam with a particle size of 2 um was added into a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73 g of conductive carbon black with a particle size of 40 nm, and mixed at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0128] Embodiment 10:

[0129] In this embodiment, compared with embodiment 1, the difference is that the ball-milled melamine foam is placed in a glass tube, and ozone gas with a mass concentration of 3ug / l is introduced at a rate of 0.4l / min, and the reaction is carried out for 10-15min to obtain the ozonized melamine foam;

[0130] The ozonated melamine foam with a particle size of 2 um was added into a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73 g of conductive carbon black with a particle size of 40 nm, and mixed at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0131] Embodiment 11:

[0132] In this embodiment, compared with embodiment 1, the difference is that the ball-milled melamine foam is placed in a glass tube, and ozone gas with a mass concentration of 20ug / l is introduced at a rate of 1.5l / min, and the reaction is carried out for 10-15min to obtain the ozonized melamine foam;

[0133] The ozonated melamine foam with a particle size of 2 um was added into a planetary mixer according to 6% of the weight ratio of the composite conductive agent and 2.73 g of conductive carbon black with a particle size of 40 nm, and mixed at a speed of 500 rpm for 15 minutes to obtain a composite conductive agent.

[0134] Embodiment 12:

[0135] In this embodiment, compared with Example 8, the difference is that 98wt% of lithium nickel cobalt manganese oxide NCM613 and 1wt% of the composite conductive agent are added to the fiberizer, mixed at a speed of 200rmp / min for 6 minutes to obtain a mixture; continue to add 1wt% of polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, and then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture.

[0136] Embodiment 13:

[0137] In this embodiment, compared with Example 8, the difference is that 94wt% of lithium nickel cobalt manganese oxide NCM613 and 3wt% of the composite conductive agent are added to the fiberizer, mixed at a speed of 200rmp / min for 6 minutes to obtain a mixture; continue to add 3wt% of polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture.

[0138] Embodiment 14:

[0139] In this embodiment, compared with Example 8, the difference is that 96wt% of nickel cobalt manganese oxide NCM613 and 2wt% of the composite conductive agent are added to the fiberizer, mixed at a speed of 200rmp / min for 6 minutes to obtain a mixture; continue to add 2wt% of polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, and then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture.

[0140] Embodiment 15:

[0141] In this embodiment, compared with Example 8, the difference is that 90wt% of lithium nickel cobalt manganese oxide NCM613 and 7wt% of the composite conductive agent are added to the fiberizer, mixed at a speed of 200rmp / min for 6 minutes to obtain a mixture; continue to add 3wt% of polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture.

[0142] Embodiment 16:

[0143] In this embodiment, compared with Example 8, the difference is that 98wt% of lithium nickel cobalt manganese oxide NCM613 and 0.5wt% of the composite conductive agent are added to the fiberizer, mixed at a speed of 200rmp / min for 6 minutes to obtain a mixture; continue to add 1.5wt% of polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture.

[0144] Embodiment 17:

[0145] In this embodiment, compared with Embodiment 1, the difference is that polyurethane foam is used to replace melamine foam to prepare the composite conductive agent.

[0146] Embodiment 18:

[0147] In this embodiment, compared with Embodiment 1, the difference is that 5 g of phenolic foam and 5 g of melamine foam are used to replace 10 g of melamine foam to prepare the composite conductive agent.

[0148] Comparative Example 1:

[0149] Preparation of positive electrode sheet (dry preparation):

[0150] S1, adding 96.5wt% of lithium nickel cobalt manganese oxide NCM613 and 2wt% of conductive carbon black into a fiberizer, mixing at a speed of 200rmp / min for 6min to obtain a mixture;

[0151] S2, continue to add 1.5wt% polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture;

[0152] S3, placing the fiberized mixture in an internal mixer and mixing it at a temperature to obtain a fiberized mixture after mixing;

[0153] S4, placing the fiberized mixture after banburying on a rolling machine for rolling to obtain a positive electrode film;

[0154] S5. At a temperature of 80° C., press the positive electrode film and the current collector to obtain a positive electrode sheet.

[0155] Comparative Example 2:

[0156] Preparation of positive electrode sheet (dry preparation):

[0157] S1, adding 96.5wt% of lithium nickel cobalt manganese oxide NCM613 and 2wt% of graphene into a fiberizer, and mixing at a speed of 200 rpm for 6 min to obtain a mixture;

[0158] S2, continue to add 1.5wt% polytetrafluoroethylene to the fiberizer, set the temperature to 10-65°C, adjust the speed to 2000rpm / min and mix for 3min, then increase the speed to 4500rmp / min and mix for 2min to obtain a fiberized mixture;

[0159] S3, placing the fiberized mixture in an internal mixer and mixing it at a temperature to obtain a fiberized mixture after mixing;

[0160] S4, placing the fiberized mixture after banburying on a rolling machine for rolling to obtain a positive electrode film;

[0161] S5. At a temperature of 80° C., press the positive electrode film and the current collector to obtain a positive electrode sheet.

[0162] test:

[0163] The positive electrode sheets, negative electrodes and separators prepared in the above embodiments and comparative examples are assembled into battery cells, loaded into a housing, and then injected with electrolyte, sealed, assembled into button batteries, and subjected to battery charge and discharge tests and EIS impedance tests (Electrochemical Impedance Spectroscopy). The test methods are as follows:

[0164] The battery capacity test is carried out on an electric test cabinet (the instrument brand is Xinwei), and the EIS impedance test is carried out on an electrochemical workstation (the instrument brand is Princeton). Specifically, the packaged battery is left to stand for 6 hours before testing. The capacity test conditions are 0.1C (1C = 215mAh / g), the voltage range is (2.8-4.45V), first constant current and constant voltage charge to 4.45V, the cut-off current is 0.01C, constant current discharge to 2.5V, and the rate is changed to 0.5C after the first cycle, and the step is set to 100 cycles. The EIS test conditions use an amplitude of 5mV and a frequency of 1MHz-0.01Hz, and the impedance information inside the battery is obtained through the equivalent circuit model. The test data is shown in the following table:

[0165]

[0166]

[0167] It should be noted that in the above table, the first discharge capacity refers to the amount of charge released by the electrode material per unit mass or volume during the first charge and discharge cycle of the battery. The first effect is the initial coulombic efficiency (ICE), which refers to the ratio of the discharge capacity to the charging capacity of the battery during the first charge and discharge process, and is expressed by the formula: first effect = first discharge capacity / first charging capacity. The 100-cycle capacity retention rate refers to the ratio of the remaining capacity to the initial capacity after the battery has been charged and discharged for 100 times, expressed as a percentage, and the calculation formula is: 100-cycle capacity retention rate = (capacity after the 100th discharge / initial discharge capacity) × 100%. The internal resistance of the battery refers to the resistance encountered by the current flowing through the battery when the battery is working.

[0168] The test conclusions are as follows:

[0169] Examples 1 to 18 compared with Comparative Examples 1 to 2: From the test results in the above table, it can be seen that the battery after using the composite conductive agent has relatively low internal resistance in the battery charge and discharge test and the EIS impedance test, which proves that in the embodiments of the present application, the battery using the composite conductive agent has better performance than the battery using the traditional conductive agent. The reason is that the composite conductive agent constructs a richer electronic conductive network than the traditional conductive agent, increases the conductive sites, and reduces the internal resistance of the battery.

[0170] In Examples 1 to 18, the test results of Examples 1 to 5 show that in Example 2, the battery internal resistance is relatively the lowest, and the first-cycle discharge specific capacity, first efficiency and capacity retention rate are relatively the highest, indicating that in the composite conductive agent provided in the embodiments of the present application, the higher the weight proportion of the ozonated melamine foam is, the better the battery performance is. The reason is that when the proportion of the ozonated melamine foam to the weight of the composite conductive agent is too low, the connection sites between the ozonated melamine foam and the conductive carbon black have not reached the richest state, and its conductive performance and other battery performance improvements are limited; when the proportion of the ozonated melamine foam to the weight of the composite conductive agent is too high, the ozonated melamine foam will partially agglomerate, which also leads to limited improvement in its conductive performance and other battery performance. Therefore, in actual application, it is necessary to appropriately adjust the proportion of the melamine foam to the weight of the composite conductive agent according to the design of the battery.

[0171] In Examples 1 to 18, in the test results of Examples 1 to 2 and Examples 6 to 7, the internal resistance values ​​of the batteries in Examples 6 and 7 are slightly lower than that in Example 2. This is because the particle sizes of the melamine foam and the conductive carbon black are relatively small. Under the same quality conditions, the specific surface area in contact with each other is larger, which is more conducive to enhancing the conductive properties of both.

[0172] In Examples 1 to 18, in the test results of Examples 1 to 2 and Examples 8 to 11, in the test data of Examples 10 and 11, the values ​​of the battery internal resistance and some other properties are higher than those of Examples 1 and 2, indicating that in Examples 10 and 11, the performance of the battery is relatively poor. This is because during the ozonation process of the melamine foam, an excessively high ozonation concentration easily leads to excessive oxidation of part of the melamine foam, destroying the basic structure of this part of the melamine foam, thereby reducing the conductive performance; and when the ozone concentration is too low, it is impossible to effectively introduce sufficient official oxygen on the surface of the melamine foam. At the same time, the flow rate of ozone will affect whether the contact between ozone and the first conductive agent is sufficient. If the ozone flow rate is too low, some melamine foams cannot fully react with ozone, and the ozonation is incomplete, which affects the consistency of the composite conductive agent. If the flow rate is too fast, it will produce physical impact. Since the particle size of the first conductive agent becomes smaller after ball milling and the physical strength is limited, high-speed flow will cause some particles to agglomerate, which will further affect the performance of the mixed composite conductive agent. Therefore, in actual use, it is necessary to adjust the appropriate ozone concentration and flow rate to ensure that the first conductive agent can be fully ozonated.

[0173] Among Examples 1 to 18, in the test results of Example 1, Example 8 and Examples 12 to 18, the data of Example 15 and Example 16 show that the performance of the battery is relatively poor, indicating that when the proportion of the composite conductive agent is low, the conductive network formed in the positive electrode material is not perfect, resulting in an increase in the resistance inside the electrode, thereby affecting the performance of the battery; when the proportion of the composite conductive agent is too high, it will occupy too much positive electrode material space, causing the relative content of the positive electrode active substance to decrease, which will cause the battery energy density to decrease, and the battery life to decrease.

[0174] Compared with Comparative Examples 1 and 2 and Implementation 1, the test data of the batteries in Examples 17 and 18 are slightly different from those in Example 1, and both can improve the relevant test performance of the batteries; this is because the polyurethane foam, phenolic foam and melamine foam all have similar carbon contents and can be further graphitized during the carbonization process. These carbon elements can form certain conductive pathways and can also be ozonated to introduce functional groups such as carboxyl and hydroxyl groups. Therefore, when used as composite conductive agents, they can improve battery performance.

[0175] See also Figure 3 and Figure 4 , Figure 3 This is a scanning electron microscope photo of carbonized melamine foam. Figure 3 In the present invention, the carbonized melamine foam has a three-dimensional structure, with a center forming convex contacts to the surroundings, which can effectively increase the contact points between the conductive agent and the active material. Figure 4 The schematic diagram of the working process of composite conductive carbon and active material is shown in Figure 2. Figure 4It can be seen that after adding the ozonated melamine foam, the ozonated melamine foam can effectively fill the gaps and contact with the conductive carbon black and active substances at the same time, which can greatly increase the conductive contact sites, make the electrical contact closer, shorten the electron transmission path, reduce the polarization of the battery, and promote the improvement of battery performance.

[0176] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a composite conductive agent, characterized in that: The following steps are involved: Carbonizing the first conductive agent in an inert gas atmosphere to obtain a carbonized first conductive agent; ball-milling the carbonized first conductive agent to obtain a ball-milled first conductive agent; ozonating the ball-milled first conductive agent to obtain an ozonated first conductive agent; The ozonated first conductive agent is mixed with the second conductive agent to obtain the composite conductive agent.

2. The method for preparing the composite conductive agent according to claim 1, characterized in that: The first conductive agent is one or more combinations of melamine foam, polyurethane foam and phenolic foam.

3. The method for preparing the composite conductive agent according to claim 1, characterized in that: The second conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes, and graphene.

4. The method for preparing the composite conductive agent according to claim 1, characterized in that: By weight, the first conductive agent accounts for 2% to 10% of the composite conductive agent.

5. The method for preparing the composite conductive agent according to claim 1, characterized in that: The particle size of the first conductive agent is 2 micrometers to 5 micrometers, and the particle size of the second conductive agent is 40 nanometers to 60 nanometers.

6. The method for preparing the composite conductive agent according to claim 1, characterized in that: In the step of ozonating the ball-milled first conductive agent to obtain an ozonated first conductive agent, the mass concentration of ozone used for ozonation is 5-15 ug / l, and the ozonation reaction is carried out with the first conductive agent at a flow rate of 0.8-1.2 L / min.

7. The method for preparing the composite conductive agent according to claim 1, characterized in that: Before the step of carbonizing the first conductive agent in an inert gas atmosphere to obtain the carbonized first conductive agent, the step further includes: acid washing, water washing and drying the first conductive agent.

8. A composite conductive agent, characterized in that: The composite conductive agent is prepared by the method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode material, and the positive electrode material comprises the composite conductive agent, positive electrode active material and binder as claimed in claim 8.

10. The positive electrode sheet according to claim 9, characterized in that: By weight, the positive electrode active material accounts for 94% to 98% of the positive electrode material, the composite conductive agent accounts for 1% to 3% of the positive electrode material, and the binder accounts for 1% to 3% of the positive electrode material.

11. A method for preparing a positive electrode sheet, characterized in that: The method for preparing a positive electrode sheet according to any one of claims 9 to 10 comprises the following steps: Mixing the positive electrode active material and the composite conductive agent uniformly to obtain a mixture; adding a binder to the mixture and performing fiberization to obtain a fiberized mixture; kneading the fiberized mixture to obtain a kneaded fiberized mixture; Rolling the kneaded fiberized mixture to obtain a positive electrode film; The positive electrode film is compounded with the carbon-coated aluminum foil to obtain the positive electrode plate.

12. The method for preparing a positive electrode sheet according to claim 11, characterized in that: The positive electrode film and the carbon-coated aluminum foil are pressed together at a temperature of 80 degrees Celsius to obtain the positive electrode plate.

13. A battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 9 to 10.

Citation Information

Patent Citations

  • Conductive composite material and preparation method and application thereof

    CN114758814A